Evidences on Molecules Most Frequently Included in Canine and Feline Complementary Feed to Support Liver Function - Andrea Marchegiani; Alessandro Fruganti; Alessandra Gavazza; Sara Mangiaterra; Alessia Candellone; Eleonora Fusi; Giacomo Rossi; Matteo Cerquetella (Veterinary Medicine International)
Numerous complementary feeds to support liver function are commercially available for small animals. Aiming to furnish a scientific support for clinicians/nutritionists that necessitate a complementary feed to support liver function in dogs and cats, with the present paper, we analyzed scientific evidences supporting the use, for this purpose, of ingredients/additives such as artichoke (Cynara scolymus), curcumin, dandelion (Taraxacum officinale), milk thistle (Silybum marianum), phosphatidylcholine, and S-adenosylmethionine. Although sustained by significant results, our review found only few scientific papers, and albeit we believe that they represent a significant aid in handling hepatopathies, in the authors’ opinion, this topic probably deserves, and would benefit of, further studies.